2015
DOI: 10.2147/ndt.s83501
|View full text |Cite
|
Sign up to set email alerts
|

The reliability and validity of a Chinese-version Short Health Anxiety Inventory: an investigation of university students

Abstract: BackgroundThe Short Health Anxiety Inventory (SHAI) is widely used in English-speaking populations, with good reliability and validity. For further research needs in the Chinese population, it was translated into a Chinese version (CSHAI). Furthermore, the reliability, validity, and cutoff score were examined in a nonclinical population in the People’s Republic of China.MethodsThree hundred and sixteen undergraduates were evaluated by a set of questionnaires including CSHAI, Zung Self-Rating Anxiety Scale (SAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 37 publications
3
29
0
1
Order By: Relevance
“…The SHAI showed good psychometric propertied in Chinese population. The Cronbach's alpha of its total and subscales were 0,742 (total), 0.743 (IL) and 0.788 (NC) [28]. In this study, the Cronbach's alphas of SHAI total and its subscales were 0.805 (total), 0.788(IL), 0.664(NC).…”
Section: The Short Form Of Health Anxiety Inventory (Shai)supporting
confidence: 49%
“…The SHAI showed good psychometric propertied in Chinese population. The Cronbach's alpha of its total and subscales were 0,742 (total), 0.743 (IL) and 0.788 (NC) [28]. In this study, the Cronbach's alphas of SHAI total and its subscales were 0.805 (total), 0.788(IL), 0.664(NC).…”
Section: The Short Form Of Health Anxiety Inventory (Shai)supporting
confidence: 49%
“…Health Anxiety The Health Anxiety Inventory (HAI) short version was used to measure participants' perceptions regarding the likelihood and feared negative consequences of becoming ill (Salkovskis et al 2002). This measure has previously been translated into Chinese (Zhang et al 2015). The HAI comprises 18 items regarding the frequency that respondents worry about health, each consisting of four statements that range from 0 to 3 (0 = never; 3 = always; Zhang et al 2015).…”
Section: Methodsmentioning
confidence: 99%
“…The measure has cognitive, autonomic, motor and central nervous system symptoms. Reliability and validity of the Chinese version have been established by many studies (e.g., Liu, Oda, Peng, & Asai, 1997; Zhang et al, 2015). Cronbach’s α in our sample for the SAS was 0.815.…”
Section: Methodsmentioning
confidence: 99%
“…Among HIV-positive former plasma/ blood donors, Meade et al (2010) reported 47% moderate and 36% severe depression, while Wang et al (2005) found that 92% of their rural sample were depressed (both studies used the Chinese version of the Beck Depression Inventory (BDI; Beck, Steer, & Garbin, 1988; Zheng, Wei, Goa, Zhang, & Wong, 1988)). Meade et al (2010) also reported that 52% met criteria for mild-moderate and 8% marked-severe anxiety (using the Chinese version of the Zung Self-rating Anxiety Scale; Zhang et al, 2015; Zung, 1971). In urban areas of Henan and Guangdong provinces, Su et al (2013) reported that 72% of their general PLWHA sample had depression.…”
mentioning
confidence: 99%